General Motors and the Sullivan Principles: how a multinational company confronted Apartheid - Fisher, Colin (Henry Stewart Talks, 2018)
This case study describes an initiative developed in 1977 by Leon Sullivan, a General Motors’ director. It was embraced by many multinationals operating in South Africa and signatories to the Sullivan Principles refused to obey Apartheid laws in the hope of shaming the South African government into abolishing apartheid. Although this proved unsuccessful, the subsequent divestment campaign launched by Leon Sullivan and General Motors contributed to the end of the Apartheid in 1994.